The Influence Of The Command Method On The Shooting Skills Of Extracurricular Futsal Students At SMPN 28 Bengkulu Utara - Faisal Ulul Azmi; Feby Elra Perdima; Lina Tri Astuty (Multidisciplinary Journals, 2026)
This study aims to determine the effect of the command method on the shooting skills of futsal extracurricular students at SMPN 28 North Bengkulu. The research employed an experimental method with a one-group pre-test and post-test design. The sample consisted of 19 students selected through total sampling. Data were collected via shooting skill tests before (pre-test) and after (post-test) 16 sessions of command method training. Data analysis included normality (Liliefors), homogeneity (F-test), and hypothesis testing (t-test). Normality test results indicated normal data distribution (Lcalculated < Ltable), and homogeneity was confirmed (Fcalculated < Ftable). The t-test yielded tcalculated=4.32 with ttable=1.752 (df=18) and p=0.00 (<0.05), leading to the rejection of H0. The mean pre-test score of 31.95 increased to 40.26 in the post-test, showing a 40% improvement in shooting skills. The command method significantly enhances the shooting skills of futsal extracurricular students at SMPN 28 North Bengkulu. These findings support the effectiveness of the command method in training basic futsal techniques, particularly shooting.